Serum Level of Homocysteine, Folate, and Vitamin B12 in Adult Epileptic Patients Under Antiepileptic Therapy (Journal of Rangpur Medical College, 2023)
Background: Epilepsy is a medical condition that requires long-term treatment with antiepileptic drugs. Different epidemiological studies revealed an increased risk of atherogenic cardiovascular diseases in patients under antiepileptic therapy. The possible etiologic suggestion is alterations of the serum homocysteine, folate, and vitamin B12 metabolism.Objective: To evaluate serum homocysteine, folate, and vitamin B12 level in patients under antiepileptic monotherapy.Methods: This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College from July 2017 to June 2018 through purposive sampling. In this study, forty diagnosed patients under antiepileptic monotherapy and forty age and sex-matched apparently healthy control were selected according to selection criteria, from OPD of the Neurology department, Dhaka medical college hospital.Results: In patients under antiepileptic therapy, mean (±SD) of serum homocysteine (μmol/L), folate (ng/ml), and vitamin B12 (pg/ml) were 14.15±3.4, 13.61±2.02, 361.78±41.26 respectively. In the healthy control group, serum homocysteine (μmol/L), folate (ng/ml), and vitamin B12 (pg/ml) were 8.78±2.59, 16.71±2.06 and 366.69±44.15 respectively. Serum homocysteine level was found higher and folate level was found lower in patients with antiepileptic therapy which were statistically significant (p